2018
DOI: 10.1111/jdv.15055
|View full text |Cite
|
Sign up to set email alerts
|

Silver absorption and toxicity evaluation of silver wound dressings in 40 patients with chronic wounds

Abstract: Both long-term application and iterative treatments with silver dressings should be discouraged, especially in the elderly, who often suffer from malnutrition and anaemia to avoid potential cumulative toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
(68 reference statements)
0
18
0
6
Order By: Relevance
“…After 3 weeks of treatment, the level of silver in blood was 194 µg/L (Chaby et al, 2005). In 40 patients with chronic wounds treated with different silver preparations, serum silver was observed to correlate to wound area (Brouillard et al, 2018). Pigs with scalds were applied 1 g of 1% silver sulfadiazine cream for 48 h; Absorption of silver was less than 1%, but silver was detected in the eye, kidney, lung, stomach, adrenal, aorta, muscle, spleen, intestine, thyroid, and brain (Lazare et al, 1974).…”
Section: Absorption Over Skin Compromised By Other Wounds and Scaldingmentioning
confidence: 99%
“…After 3 weeks of treatment, the level of silver in blood was 194 µg/L (Chaby et al, 2005). In 40 patients with chronic wounds treated with different silver preparations, serum silver was observed to correlate to wound area (Brouillard et al, 2018). Pigs with scalds were applied 1 g of 1% silver sulfadiazine cream for 48 h; Absorption of silver was less than 1%, but silver was detected in the eye, kidney, lung, stomach, adrenal, aorta, muscle, spleen, intestine, thyroid, and brain (Lazare et al, 1974).…”
Section: Absorption Over Skin Compromised By Other Wounds and Scaldingmentioning
confidence: 99%
“…is can be explained by bacterial resistance due to overuse or inappropriate use and cytotoxicity of antibacterial molecules, which are barriers to healing and harmful for the patient [21]. ese products are also expensive [5,[21][22][23]. Few occurrences of resistance to silver have been reported in the medical literature, and the cellular sensitivity is correlated with the level of silver release and exposure [14,15,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that at a higher concentration of silver nanoparticles, undesirable side effects, including argyria and limited proliferation and metabolic activity of keratinocytes, were observed. [22][23][24] As indicated earlier, the motivation behind inclusion of silver in the ROCF-ciNPT skin interface layer is to minimize the microbial growth within the dressing itself, and not to induce a localized antimicrobial effect (i.e., at the wound site or incision site) to prevent and/or manage the infection at the surgical site. Thus, we set to determine the effect of silver present in the ROCF-ciNPT skin interface layer on microbial growth when it is placed in direct contact with a microbial colony.…”
Section: Limited Silver Mobility and Subsequent Zone Of Inhibitionmentioning
confidence: 99%